TEACHER’S MUSIC ACTIVITIES IN THE CLASSROOM AS A PREREQUISITE FOR IMPROVEMENT OF MUSIC EDUCATION - Rauduvaite, Asta; Li, Yanran (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The relevance of the research is realized through the search for the music teacher’s activities that help to improve the process of music education while fostering the learner’s aesthetic and meaningful relationship to music. The object of the research is a music teacher’s activity of teaching music in general education school. The aim of the research is to analyse the improvement opportunities of a music teacher’s activity during music lessons in seventh-eighth grades in general education schools. The methods of the research include the analysis of scientific literature and documents of education; semi-structured interviews with music teachers; a written survey; quantitative and qualitative data analysis. According to the collected data, a variety of musical activities helps to develop learners’ inborn musical abilities, provide a favourable learning environment with an opportunity to develop the learners’ musicianship and presuppose their transferable skills. In this context, teachers’ active and creative musical involvement helps the learner to experience more positive emotions. Such a personal involvement and cooperation serve as a major condition for the improvement of the teachers’ musical activity. An inappropriate choice of the activities can lead to dissatisfaction and be the main reason for failure. The teachers’ participation in musical activities could encompass a number of music modes, which could create a more attractive and productive activity in the lesson: a teacher – a performer – a listener – a facilitator – a leader.